2016
DOI: 10.18677/encibio_2016b_020
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Fenológica De Três Espécies Florestais Em Ecossistema De Terra Firme, Amapá, Brasil

Abstract: RESUMO O objetivo deste trabalho foi obter informações referentes à fenologia reprodutiva de três espécies florestais: Carapa guianensis Aubl., Caryocar villosum (Aubl.) Pers. e Virola melinonii (Benoist) A.C.Sm., em floresta de terra firme. O estudo foi desenvolvido no município de Porto Grande, Amapá. Foram selecionadas 10 matrizes de cada espécie e observadas a floração, frutificação e mudança foliar para cada árvore por um período de 28 meses. A floração das espécies V. melinonii, C. villosum ocorreu duran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…According to Oliveira (2008) and Faria et al (2015), fruit from Cerrado plants typically matures heterogeneously across the biome, with a tendency for fleshy fruits to set and spread during the rainy season in such a way that they are synchronized with the increased activity of their seed dispersers during this period of the year. Similar to our findings, Freitas et al (2016) performed a phenological characterization study of three forest species from 1997 to 1999 and found that C. villosum set from November to March, a period coinciding with the rainy season.…”
Section: Discussionsupporting
confidence: 88%
“…According to Oliveira (2008) and Faria et al (2015), fruit from Cerrado plants typically matures heterogeneously across the biome, with a tendency for fleshy fruits to set and spread during the rainy season in such a way that they are synchronized with the increased activity of their seed dispersers during this period of the year. Similar to our findings, Freitas et al (2016) performed a phenological characterization study of three forest species from 1997 to 1999 and found that C. villosum set from November to March, a period coinciding with the rainy season.…”
Section: Discussionsupporting
confidence: 88%